A preliminary study of the use of new and old media among youths in Malaysia - Wong, Su Luan; Tamam, Ezhar; Hamzah, Azimi; Yee, Wendy Mei Tien; Idris, Fazilah; Mohd Ayub, Ahmad Fauzi; Atan, Hanafi (Malaysian Educational Technology Association, 2007)
This paper reports upon a preliminary descriptive study that was conducted to assess youths’ use of new and old media (television, newspaper, magazine, radio and the Internet) to obtain news related information. In addition, this study further investigated the amount of attention that youths give to such media and how the use of new and old media relate to one another. A total of 3325 youths between the ages of 15 and 39 participated in this study. It appears that the vast majority of youths watch the television very frequently to find out about news related information. It was also found that they give the most attention to news related information obtained from such medium. Old media such as the television, newspaper and radio are moderately related with one another but are poorly related to new medium such as the Internet. In conclusion, this nationwide survey reveals that older media still dominate the lives of youths in Malaysia and there is no indication that the Internet adversely affects the old media.